Loanwords - karl Jurgen Kampmark (Journal of Modern Languages)
This paper attempts to discuss some aspects of the phenomenon which it is usually called 'loanword'. The paper intends to bring to light some unfamiliar facts about the ways in which people of different language communities react when faced with the appearance of loanwords. Finally, it seeks to provide a satisfactory answer to the implied question in the title that who needs loanwords.